Attitude is everything: Youth attitudes, gang involvement, and length of institutional gang membership. (November 2014) - Scott, Daniel W.
Prison gangs have been a topic of interest among scholars, but research on youth prison gangs is limited. Furthermore, violent attitudes and gang involvement have not been addressed extensively, and a better understanding of youth prison gang involvement is needed to effectively inform responses to violence in correctional facilities. This paper fills this research gap through an analysis of violent attitudes as they relate to gang involvement and length of gang membership. The data derive from interviews with 285 males conducted in a larger study on gangs and violence in California's youth correctional facilities. The results show that gang members tend to have stronger violent and aggressive attitudes compared to nongang members, and length of institutional gang membership is statistically significant and negatively associated with violent and aggressive attitudes. Furthermore, a youth's violent and aggressive attitudes will vary depending on if the youth has never spent time in an institutional gang, is currently in one, or is a former institutional gang member. I conclude the paper with a discussion of these findings and what they imply for gang group processes, theory, institutional policy, and programs.